Hierarchical porous activated carbon for supercapacitor derived from corn stalk core by potassium hydroxide activation. (10th September 2016) - Cao, Yuhe; Wang, Keliang; Wang, Xiaomin; Gu, Zhengrong; Fan, Qihua; Gibbons, William; Hoefelmeyer, James D.; Kharel, Parashu Ram; Shrestha, Maheshwar
Highlights: Hierarchical porous active carbons was prepared from spongy corn stalk core. BET surface area of 2495 m 2 g −1 and a pore volume of 1.23 cm 3 g −1 were obtained. Nanostructured carbon with high capacitance >300 F g −1 from corn stalk core. 0.40 cm 3 g −1 (<1.1 nm) ultramicropore was generated for CSC-700. Abstract: Hierarchical porous activated carbon (AC) was obtained from corn stalk pith with a hierarchical macroporous nature, which is composed of cells of soft and spongy texture. The high specific surface area (2495 m 2 g −1 ) of the activated carbon (AC) was produced by the activation of corn stalk core (CSC) using potassium hydroxide at 700 °C. SEM, TEM and XRD were used to test the microstructure and crystallographic orientation of the carbon samples. The cyclic voltammetry, galvanostatic charge/discharge and electrochemical impedance spectroscopy were measured based on CSC-700. This sample had relatively low inner resistance of 1.0 Ω. The specific capacitance was 323 F g −1 in 6 mol L −1 KOH electrolyte at a current density of 0.1 A g −1, and it still maintained very good cyclic stability with capacitance retention ratio of 97.9% (from 265.0 to 262.4 F g −1 ) at current density of 1.0 A g −1 for 1000 cycles.